PELAYANAN PASIEN RAWAT INAP DI RUMAH SAKIT SANTO ANTONIUS PONTIANAK - Yohanes Viany E.21109021 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Thisarticleis intendedtodeterminethe quality ofpatientcareatthe hospitalof Saint AnthonybornebyPT.JamsostekPontianakin West Kalimantancoversthreeaspectstodescribethe data/factsare encounteredin the hospitalof St. AnthonyPontianakin accordancewith what it isaboutquality of serviceare:a)    To knowandanalyzethe quality ofpatientcareatSt. AnthonyHospitalPontianakbyPT. JAMSOSTEKwestKalimantanseenfrom the aspect ofstructure.b)    Toidentify and analyzethe quality ofinpatient care atSt. AnthonyHospitalPontianakbyPT. JAMSOSTEKWestKalimantanseenfrom the aspect ofthe process.c)     To knowknow and analyzethe quality ofpatientcareatSt. AnthonyHospitalPontianakbyPT. JAMSOSTEKwestKalimantanseenfrom the aspect ofOutcome.The results showedthatallaspects of theservicesunder studyaffect thequalityandsatisfaction ofthe Social Securitypatients. The thirdaspect ofthestructure, processandoutcomegreatlyaffectservice satisfactioninfluence theexpectationsandrealitypesianparticipantswhoreceivedSocial Security. Although thequality of services providedby the hospitalof St. AnthonyPontianakagainstthe Social Securitypatientsnot fullymeet theexpectations ofthe Social SecuritypatientsbutHis ministryhas beenquitegood.Keywords: Quality of carein terms of aspectsStructure, ProcessandOutcome